Fenomena Pengendara Motor Di Bawah Umur - Nugraha, Ilham; Syaripulloh, Syaripulloh; Nourwahida, Cut Dhien; Fajarini, Ulfah; Zaharah, Zaharah (Jurnal Ilmiah Wahana Pendidikan, 2025)
The research aims to understand the Phenomenon of Underage Motorcycle Riders (A Case Study of Students at SMP Negeri 1 Gunungputri. This research uses descriptive qualitative research methods with a case study approach. Data collection techniques include interviews, observation, and documentation. Data analysis techniques using Miles and Huberman model. The research sample consists of 4 students from SMP Negeri 1 Gunungputri, 4 parents, 1 school representative, 2 community members, and 1 law enforcement officer.. The results show that the factors behind underage motorcycle riders using motorcycles include personal factors, family factors, and peer factors. Underage motorcycle riding also has both positive and negative impacts; the positive impact includes mobility from home to school, while the negative impact includes traffic accidents. There are three efforts made to address underage motorcycle riding: first, efforts made by parents, such as prohibiting speeding and always wearing a helmet when riding a motorcycle. Second, efforts made by the school, such as conducting socialization about traffic rules and motorcycle riding in collaboration with the police during the MPLS (School Environment Introduction Period) event. Third, efforts made by law enforcement, such as conducting socialization at schools during Monday morning assemblies, as well as repressive measures like issuing traffic tickets while simultaneously providing education about traffic rules.